2019
DOI: 10.5815/ijem.2019.04.04
|View full text |Cite
|
Sign up to set email alerts
|

PID Control Design for Second Order Systems

Abstract: The Proportional Integral Derivative (PID) controllers are most commonly used in industries to compensate several numbers of practical industrial processes by the virtue of their simplicity and robustness. Several tuning methods exist for parameter tuning of PID controller. In this paper PID control design for second order system has been done with various methods. The effectiveness of tuning methods has been compared based up on time response specifications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 14 publications
0
1
0
Order By: Relevance
“…There are several techniques that have been proposed for tuning the gain of a PID controller, including the Ziegler and Nicholas (ZN) method [65], [66], [67], [68], the Modified ZN (MZN) method [69], [70], [71], the Tyreus-Luyben (TL) method [72], [73], [74], and the CHR tuning method [75], [76]. These techniques can be applied in both open-loop and closed-loop control modes and can be used to find the gain values for a system by substituting known values into preestimated equations or tables.…”
Section: Introductionmentioning
confidence: 99%
“…There are several techniques that have been proposed for tuning the gain of a PID controller, including the Ziegler and Nicholas (ZN) method [65], [66], [67], [68], the Modified ZN (MZN) method [69], [70], [71], the Tyreus-Luyben (TL) method [72], [73], [74], and the CHR tuning method [75], [76]. These techniques can be applied in both open-loop and closed-loop control modes and can be used to find the gain values for a system by substituting known values into preestimated equations or tables.…”
Section: Introductionmentioning
confidence: 99%
“…The most popular control method in these systems is the PID control system [32], [33], [34], [35], [36], [37]. Other techniques that have been proposed include the Arte Ziegler and Nicholas (ZN) method [38], [39], [40], [41], the modified ZN (MZN) method [42], [43], [44], the Tyreus-Luyben (TL) method [45], [46], [47], and the CHR tuning method [48], [49]. These techniques can be used in both open-loop and closed-loop control modes and can be used to find the gain values for a system by substituting known values into preestimated equations or tables.…”
Section: Introductionmentioning
confidence: 99%
“…For such a system, it is better to have a model based on system identification or empirical modeling [9]. The PID controller is the most common control algorithm [10,11,12]. A survey has shown that 90% of control loops are PI and PID structures [13,14].…”
Section: Introductionmentioning
confidence: 99%